Breakdown pathways during oral processing of different breads: impact of crumb and crust structures. Issue 3 (9th February 2016) - Jourdren, S.; Panouillé, M.; Saint-Eve, A.; Déléris, I.; Forest, D.; Lejeune, P.; Souchon, I.
Abstract : An in vivo approach permitted to determine the respective contribution of bread properties and physiology characteristics to oral breakdown pathways. Abstract : Oral processing during bread consumption is a key process related to the dynamics of texture perceptions, sensory stimuli release and starch digestion. The aim of this study was to determine the respective contribution of bread properties (composition and structure of crumb and crust) and of the oral physiology of subjects to the breakdown pathways in the mouth. The properties of the in vivo bread bolus obtained from eight healthy subjects were studied at three key points in time during their oral processing. The progressive lubrication and breakdown of bread were observed, as well as the beginning of the enzymatic degradation of starch. The study showed that "time" was the factor responsible for the greatest variability in bolus properties. Breakdown pathways were established for crumbs with and without crust. The presence of crust modified the oral processing, increasing, for instance, the heterogeneity of particle size at the middle of the oral processing sequence. Moreover, the hydration capacity of crust contributed to high starch degradation at swallowing time, in comparison with crumb alone. The main subject characteristics impacting bolus properties were the in-mouth duration, the individual masticatory index and the mouth volume, while the main bread properties explaining the bolus properties were the initial composition and the water-absorbing capacity. We concluded that both crumb and crust structures had an impact on the oral processing, affecting the capacity of hydration, the rheology and the breakdown degree of the bolus.